Efeito dos tratamentos de superfície na resistência da união porcelana/cimento resinoso - Nagayassu, Marcos Paulo [UNESP] (2003)
The aim of this ln vitro study was to evaluate the effect of different surface treatments on the shear bond strength between porcelain and resin cement. Sixty pairs of 50% aluminous porcelain (Vitadur Alpha - Vita) discs were fabricated, each with 6mm in diameter by 3mm in thickness (A), and 3 by 3mm (B). Samples were randomly divided into six groups (n=10), according to one of the following surface treatments: etching with 10% hydrofluoric acid for 2 or 4min (G1 and G2); sandblasting with aluminum oxide (50µm) for 5s (G3); sandblasting followed by etching for 2 or 4min (G4 e G5) and control (G6). Then, silane was applied (Tokuso Ceramic Primer- Tokuyama) on the treated surface of both discs, and using a dual-cure resin cement (Bistite ll DC- Tokuyama), B discs were bonded together with their respective A discs. Specimens were stored in distilled water at 37ºC for 24h before shear bond strength were determined on a universal testing machine. The results, in MPa, were compared by one-way ANOVA and Tukey test (p≤0,05). Bond strength produced alter etching with 10% hydrofluoric acid for 2min was significantly higher than etching for 4min and control, but there was no statistical difference to sandblasting a/one, or followed by etching for 2 or 4min